Analisis Dampak Kenaikan BBM Terhadap Biaya Transportasi Perdagangan Internasional - Pratama Putra Kartia; Nadiyah Putri Hapsari; Aqila Gema Nuswantoro; Heksa Bintang Pamungkas (Universitas 45 Surabaya, 2023)
The increase in the price of Fuel Oil (BBM) has significant implications for transportation costs in the context of international trade. This research aims to conduct a comprehensive analysis of the impact of BBM price hikes on transportation costs and their implications for the dynamics of global trade. The research methodology employed involves a qualitative approach to gain comprehensive insights. A literature review identifies the complex relationship between fluctuations in crude oil prices, BBM subsidy policies, and the transportation costs of international trade. Focusing on companies, this research explores perspectives and experiences from various stakeholders. Data analysis involves selecting samples from companies and fuel users with significant transportation costs exposure. Statistical data, including BBM prices, transportation costs, and trade volumes, are analyzed using descriptive statistical methods and regression analysis to identify relationships between variables. The research findings are expected to provide a profound understanding of the impact of BBM price increases on transportation costs and offer guidance for businesses and government policies. The implications of this analysis can assist in formulating effective adaptation strategies to address the challenges of fluctuating BBM prices, thereby enhancing a country's economic competitiveness in international trade. This research is anticipated to contribute to scholarly literature and provide practical insights for stakeholders involved in international trade.